Crossword Plants: Developing an Audio-Visual Interactive Multimedia to Improve Fourth-Grade Students’ Learning Outcomes on Plant Parts - Nerina Tita Rahmadani; Wahyudi Wahyudi; Aprilia Dwi Handayani (BIOCHEPHY: Journal of Science Education, 2026)
This study was motivated by the low learning outcomes of fourth-grade students at SDN Keniten 1 on the topic of plant parts, caused by limited student engagement and the use of less interactive learning media. The study aimed to develop an audio-visual Crossword Plants-based interactive multimedia that is valid, practical, and effective in improving students’ learning outcomes. The research employed the Research and Development (R&D) method using the ADDIE model, comprising five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects were 24 fourth-grade students of SDN Keniten 1. Data were collected through observation, interviews, questionnaires, and tests. The results showed that the developed interactive multimedia achieved a validity score of 78% from media experts (feasible category) and 91% from material experts (highly feasible category). The practicality level reached 96% based on teacher responses, 100% in the limited trial, and 97.5% in the large-scale trial, all categorized as highly practical. The effectiveness of the media was indicated by classical learning mastery of 87.5% in the limited trial and 93.75% in the large-scale trial, along with N-Gain scores of 0.75 and 0.76, both in the high category. Furthermore, the Paired Sample t-Test results showed a Sig. (2-tailed) value of less than 0.05, indicating a significant difference between students’ pretest and posttest scores after using the media. Therefore, the audio-visual Crossword Plants-based interactive multimedia was found to be valid, practical, and effective in improving the learning outcomes of fourth-grade students at SDN Keniten 1 on the topic of plant parts.